Technical-tactical actions of fighters specialized in striking, grappling, and mixed combat in the Ultimate Fighting Championship - Fernandes, J. R.; de Brito, M. A.; Brito, C. J.; Aedo-Munoz, E.; Miarka, B. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. This study aimed to describe and analyze the technical-tactical actions used by fighters who had already had experience in striking, grappling, and mixed combat sports when joining the Ultimate Fighting Championship® (UFC®). Methods. The present research analyzed 384 athletes` performance, classified as grappling, striking, or mixed athletes during combat during their initial performance in UFC® (<3 months) and at a second time, (>6 months of UFC®). The analyzed data compared the striking, grappling, and mixed techniques, p<0.05. Results. Differences were found between groups regarding the percentage of actions, as athletes who entered from mixed combat sports backgrounds used a lower percentage of striking actions, in both the primary [41 (32.3; 51.5); p=0.001] and secondary [40 (35.3; 46.0); p=0.001] modules, as well as in grappling techniques [32.0 (17.5; 41.5); p=0.001]; and high draw outcomes [1.0 (0.0; 3.0); p=0.001]. For the outcomes, strikers ended the combat by knockout/technical knockout [8.0 (4.0; 11.0); p=0.001]. For the secondary module, defeat [5.0 (1.0; 10.0); p=0.001], tie [0.5 (0.0; 2.0); p=0.001] and referee decision [4.0 (3.0; 7.0); p=0.001] were predominate in the mixed athletes; knockout/technical knockout [7.0 (4.0; 10.0); p=0.001] and submission [3.0 (1.0; 6.0); p=0.001] predominated in strikers. Conclusions. The present results show that specific technical actions differentiate athletes who previously practiced striking and grappling combat sports. There is special attention given to athletes coming from mixed sports, who had a better pacing strategy but fewer attacks.